Feed-Interval Scallop Height Estimation Using Multi-axis CNC Milling Machine - Xiao Zhong, Hao; A.A.Duroobi, Ahmed; Wenliang, Chen (Anbar Journal of Engineering Sciences, 2012)
This research presents a mathematical model of feed-interval scallop height, where in a machined surface there are two types of scallop height, the pick(path)-interval scallop and the feed-interval scallop. The pick-interval scallop is generated by the finite pick offset between the successive cutting paths, while the feed-interval scallop is generated by the finite increment between the successive tooth feeds. New model that describes and predicts the geometric generating mechanisms of the feed-interval scallop height have been derived using torus cutter which is commonly used in multi-axis milling machine. The machining parameters (effective tool cutter radius, feed per tooth and the magnitude of tool axis inclination angles) have been considered in theoretical and experimental work to study the effect of these parameters on this type of scallop height. From theoretical and experimental work it was found that at high-speed machining, the feed-interval scallop is more important to the surface roughness than the path-interval scallop, and the feed-interval scallop is very sensitive to the tool-axis inclination angle. The feed-interval scallop height decreased sharply and quickly within a few degrees of the tool-axis inclination to the normal workpiece surface. In general, an inclination angle equal to is good enough for all tool diameters used in the present work, namely (6,8,10 12 mm).